Evaluation of the helium hermeticity reliability of copper through-glass vias. (October 2022) - Okoro, Chukwudi; Maurey, Pamela; Davis, Ronald; Pollard, Scott
Abstract: This work aims to understand and assess the helium hermeticity reliability of metallized copper (Cu) through-glass vias (TGVs) made in Corning® HPFS® Fused Silica glass substrate. To assess this, the Cu TGV wafers were subjected to numerous stringent environmental reliability tests that includes high temperature storage (HTS) at 125 °C, highly accelerated stress testing (HAST), 130 °C/85 % RH and thermal shock (−40 °C/125 °C). Using a helium leak rate of >1.0 × 10 −8 atm·cm 3 /s as the failure criteria, it was found that all the Cu TGV wafers used in this study significantly outperformed specification requirements, irrespective of the harsh environmental conditions that they were subjected to. This finding clearly attests to the robustness and suitability of Cu TGV wafers used in this study for stringent helium hermeticity requirement applications. At the completion of the tests, no failures were found for all samples subjected to thermal shock and HTS even after 9000 cycles and 4600 h respectively. For HAST samples that failed after exposure times of 400 h and 1500 h, it was found that the root cause for their failure was due to the erosion of Cu at the titanium (Ti)–Cu interface, caused by the formation of CuO and/or Cu2 O. This led to sidewall debonding of the Ti–Cu interface, resulting in helium leak rates > 1.0 × 10 −8 atm·cm 3 /s. Additionally, higher HAST exposure time was found to lead to increased degradation of the Ti–Cu interface. Highlights: Assessed the helium (He) hermeticity performance of Cu TGV wafers, subjected to different harsh environmental conditions Cu TGV wafers exceedingly outperformed specification requirements, while maintaining a He leak rate of < 1.0e-8 atm.cc/s HAST was the most detrimental test to the He hermeticity performance of Cu TGV wafers, compared to other reliability tests